Constrastive-Comparative Study on Students' Perceptions of Using Literary Texts as Authentic Language Learning Resources - Lilia Petriciuc (National Centre for Policy and Evaluation in Education, 2019)
This comparative study represents an attempt to identify students' perceptions and needs at the same time, in terms of incorporating literary texts in the foreign language class. For quite a long time literary texts (LT) have been massively marginalized as a language learning resource and consequently students display significant deficiencies in interpreting figurative language, making inferences, thinking critically. The researcher assumes that revitalizing LT in the language class would bring multiple benefits to the students who learn EFL as part of a double program training them to become teachers of other subjects as well as primary and secondary school teachers in Moldova. It is a contrastive-comparative study involving 83 students, 48 undergraduates from the University of Granada and 35 from SPU "Ion Creangă" of Chişinău, Moldova. The data were collected through mixed instruments: all of the students filled in a survey for quantitative data and the students from Moldova participated in a semi-structured interview at the end of their 2nd year course in English. The findings reveal rather positive attitudes in favor of LT as a language learning resource, but at the same time there are differences between the perceptions of Spanish and Moldovan students. The pedagogical implications of the study for stakeholders at "Ion Creangă" University suggest reconsidering the EFL curriculum with a view of incorporating more LT alongside other types of authentic materials used to develop students' language proficiency.